Réponses

2014-03-02T17:17:48+01:00


A= (-2) x 8 + 5 x 4 + (-6) x (-3)

A= -16 + 20 + 18

A= 4 + 18

A= 22


B= 4 - (-5) x (-2) + (3 - 4 x 2)

B= 4 - 10 + (3 - 8)

B= -6 + (-5)

B= -6 - 5

B= -11


C= 5 x (-2) + (-5 - 3 x (-5)) + (8 x (-2) + 3)

C= -10 + (-5 - (-15)) + (-16 + 3)

C= -10 + 10 + (-13)

C= 0 - 13

C= -13


D= 175 x (-125 : 5 + (-3) x (-2))

D= 175 x (-25 + 6)

D= 175 x (-19)

D= -3325


E= (-5 + 3) x (-10) + (-2-3) x 5 + 35/7

E= -2 x (-10) + (-5) x 5 + 35/7

E= 20 + (-25) + 5

E= 20 - 25 + 5

E= -5 + 5

E= 0